2021
DOI: 10.1051/0004-6361/202140720
|View full text |Cite
|
Sign up to set email alerts
|

Forever young white dwarfs: When stellar ageing stops

Abstract: White dwarf stars are the most common end point of stellar evolution. The ultramassive white dwarfs are of special interest as they are related to type Ia supernovae explosions, merger events, and fast radio bursts. Ultramassive white dwarfs are expected to harbour oxygen-neon (ONe) cores as a result of single standard stellar evolution. However, a fraction of them could have carbon-oxygen (CO) cores. Recent studies, based on the new observations provided by the Gaia space mission, indicate that a small fracti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 66 publications
4
39
0
1
Order By: Relevance
“…Cheng, Cummings & Ménard (2019) later demonstrated that about 6 per cent of high-mass white dwarfs (M > 1.05 M ) on this transverse sequence, likely the products of double-degenerate mergers, must experience an extra 8 Gyr cooling delay not explained by core crystallization alone. More recently, Blouin, Daligault & Saumon (2021) reconciled these results showing that a distillation process during 22 Ne phase separation in crystallizing white dwarfs could explain both the cooling delay of standard white dwarfs and the extra delay experienced by high-mass double white dwarf mergers (see also Bauer et al 2020;Camisassa et al 2021). A number of additional studies have focused on the spectral properties of ultramassive white dwarfs, consolidating the idea that many of these systems are the result of double white dwarf mergers (Hollands et al 2020;Kawka, Vennes & Ferrario 2020;Kilic et al 2021).…”
mentioning
confidence: 91%
“…Cheng, Cummings & Ménard (2019) later demonstrated that about 6 per cent of high-mass white dwarfs (M > 1.05 M ) on this transverse sequence, likely the products of double-degenerate mergers, must experience an extra 8 Gyr cooling delay not explained by core crystallization alone. More recently, Blouin, Daligault & Saumon (2021) reconciled these results showing that a distillation process during 22 Ne phase separation in crystallizing white dwarfs could explain both the cooling delay of standard white dwarfs and the extra delay experienced by high-mass double white dwarf mergers (see also Bauer et al 2020;Camisassa et al 2021). A number of additional studies have focused on the spectral properties of ultramassive white dwarfs, consolidating the idea that many of these systems are the result of double white dwarf mergers (Hollands et al 2020;Kawka, Vennes & Ferrario 2020;Kilic et al 2021).…”
mentioning
confidence: 91%
“…Cheng et al, (2019) noticed that this overdensity is placed near the crystallization point of M ≳ 1 M ⊙ and it cannot be accounted with the standard C/O model suggesting the gravitational settling of 22 Ne as the extra source of energy necessary to introduce a substantial delay in the cooling of Ħ 8 Gyr. Furthermore, Bauer et al, 2020 have shown that this branch is consistent with the solidification of C/O cores but not with the O/Ne ones, and Camisassa et al, (2021) that this cores must be massive and have neon abundances as large as X 22 ]Ne) Ħ 0.06 to obtain the required effects in contradiction with the evolution of single stars. On the contrary, if the phase diagram of Blouin et al, (2021) is correct it would be possible to explain the origin of the Q-branch and, perhaps, to open the possibility of relating the meteoritic neon-E anomaly with the collision of two white dwarfs in which, at least one of them, has a pure C/Ne shell (Isern and Bravo, 2018a,b).…”
Section: Conductivitiesmentioning
confidence: 92%
“…According to cooling models of WD, the UMWDs in Q branch that experience extra cooling delay may stem from CO WDs with an enhancement of 22 Ne (e.g. Bauer et al 2020;Camisassa et al 2021). The enhancement of 22 Ne in a WD is likely due to that the progenitor of the WD is metalrich (e.g.…”
Section: Initial Metallicitymentioning
confidence: 99%